Crystal structure of methyl 3-(1,3-dioxo-1H-benzo[de]isoquinolin-2(3H)-yl)propanoate, C16H13NO4 - Wang Tiantian; Su Yizi; Feng Yunyun; Deng Xin; Tan Yuxing (Zeitschrift für Kristallographie - New Crystal Structures)
C16H13NO4, monoclinic, P21/c (no. 14), a = 9.930(3) Å, b = 6.9807(18) Å, c = 18.954(5) Å, β = 93.080(4)°, V = 1311.9(6) Å3, Z = 4, R gt(F) = 0.0400, wR ref(F 2) = 0.1142, T = 296 (2) K.